Complex reconstruction of the perineal and gluteal regions after resection of a large squamocellular carcinoma of the anal margin: a case report - Walter Ferraz Flávio Júnior; Bruno Rabelo Bernardes; Thaís Aparecida de Souza Silva; Henrique Xavier Miranda Capanema; Fabrício Nishimoto; Paulo Roberto da Costa (Revista Brasileira de Cirurgia Plástica, 2016)
Perineal and gluteal regions may be affected by a wide spectrum of diseases, and the treatment may require extensive surgery and cause functional, aesthetic, and psychosocial damages at various levels. Wounds in the extensive perineal and gluteal regions after surgical treatment of neoplasia may represent a challenge in local reconstruction. Size, location, and availability of tissue around the lesion may hinder wound primary closure, requiring the use of one or more flaps. This article reports a case of reconstruction of the perineal and gluteal regions after oncological resection at the plastic surgery service of the Hospital das Clínicas at the Federal University of Minas Gerais. The muscle and fasciocutaneous flaps of the gluteus maximus and myocutaneous of the semimembranosus were used.